Warm peace - Cordovez, Diego (2016)
This article reviews the most important events in the international relations field that have happened since the publication of our last issue. The author analyzes the steps that the United States and other governments have undertaken in their campaign against terrorism since September 11. lt is stated that the political stabilization and reconstruction of Afghanistan has not been successful, a disappointing outcome which could lead to a renewal of political fights and even to a new civil war. The author critically addresses the current state of the Middle East's conflict, the old controversies bet-ween India and Pakistan, and the Latin American economic turmoil and political instability.